Role of G-protein alpha sub-units in the morphogenic processes of filamentous Ascomycota fungi - García-Rico, Ramón O; Fierro, Francisco (Revista iberoamericana de micologia, 2017)
The phylum Ascomycota comprises about 75% of all the fungal species described, and includes species of medical, phytosanitary, agricultural, and biotechnological importance. The ability to spread, explore, and colonise new substrates is a feature of critical importance for this group of organisms. In this regard, basic processes such as conidial germination, the extension of hyphae and sporulation, make up the backbone of development in most filamentous fungi. These processes require specialised morphogenic machinery, coordinated and regulated by mechanisms that are still being elucidated. In recent years, substantial progress has been made in understanding the role of the signalling pathway mediated by heterotrimericG proteins in basic biological processes of many filamentous fungi. This review focuses on the role of the alpha subunits of heterotrimericG proteins in the morphogenic processes of filamentous Ascomycota.